Pemanfaatan Media Manipulatif Dalam Meningkatkan Pemahaman Konsep Matematika di SD/MI : Kajian Teoritis dan Praktis - Aini, Intan Nur; Amrulloh, Hanif (Indonesian Journal of Learning and Instructional Innovation, 2025)
Mathematical concepts understanding at the elementary school level is often hampered by the abstract and lack of contextual nature of the material. This study aims to theoretically analyze the role of manipulative media in improving mathematical concept understanding and active student engagement. The method used is a literature study with a descriptive analysis approach to various academic sources from the last ten years (2015-2025). The findings indicate that manipulative media functions as a cognitive bridge that transforms abstract concepts into concrete experiences through tactile and motor interactions. The integration of manipulative media with the Problem-Based Learning (PBL) model has been shown to improve memory retention, reduce mathematical anxiety, and strengthen students' problem-solving skills. This study also highlights the transformation of manipulative media from physical to digital forms, such as GeoGebra and AI-based simulations, which offer greater flexibility in modern learning. The novelty of this article lies in the complementary synthesis of physical and digital media within the framework of Piaget's and Vygotsky's constructivist theories. The conclusion of this study emphasizes that the use of adaptive and innovative manipulative media is a primary prerequisite for creating meaningful mathematics learning at the elementary school level.